Translating exercise biology into the Venezuelan medical education and health care system. - Del Corral, Pedro (Investigación Clínica, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Caslon224 Bk BT"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"Times New Roman"; mso-font-charset:0; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 0 0 0 0 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>In the absence of pharmacological agents, physical exercise was widely used by physicians in the late 19th century to treat a number of maladies. In the 1950”™s, epidemiological evidence suggested an association between physical activity and health, and increased interest in clinical exercise biology. By the 1990”™s, sufficient research data was accumulated on the benefits of exercise, such that North American medical associations, government agencies, and the World Health Organization have published guidelines on exercise for public and clinical populations. Despite this, leaders in medical education have remained reluctant to incorporate exercise biology into the core medical curriculum, or to systematically implement it in graduate medical education. This work reviews Venezuelan exercise biology literature, and its medical applications. Venezuelan scientists and clinicians have invested efforts in cardiopulmonary exercise testing, skeletal muscle adaptations to training and exercise cardiovascular pharmacology in patients, sedentary subjects and athletes. It is suggested here, that there is a need to develop education and research programs in basic and clinical exercise biology in the formal training of medical students, physicians in residency programs, and allied health care professionals. Tentative steps to initiate this process are proposed.